The Effectiveness of a Rational Emotive Behavior Therapy Group Setting in Reducing Egocentrism in Bullying Perpetrators - Saragih, Nur Afifah Nabila; Firman, Firman (Universitas Ahmad Dahlan, 2024)
Bullying among adolescents in Indonesia frequently occurs and has shown an increase. Adolescents tend to engage in bullying, partly due to egocentric thinking, which involves difficulty in distinguishing their own perspective from that of others. This study aims to determine the effectiveness of the rational emotive behavior therapy approach in a group setting in reducing the egocentrism of bullying perpetrators. This research employs a quantitative experimental approach using a Control Group Pretest-Posttest design. The study involves 218 students from SMA Negeri 10 Medan who were identified as bullying perpetrators. The sample consists of 16 students selected through purposive sampling. The research instrument is a scale measuring the egocentrism of bullying perpetrators. Data analysis was conducted using the Wilcoxon test and the Mann-Whitney U test. The results indicate that the rational emotive behavior therapy approach is effective in reducing the egocentrism of bullying perpetrators.